Mating à la Spence: Deriving the Market Demand Function for Status Goods - Tobias Thomas (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2007)
Conspicuous consumption of luxuries plays a central role in the work of Thorstein B. Veblen. More recently, interpersonal effects have emerged as an important factor in consumption theory. However, the inadequate modelling of individuals' interaction often leads to questionable results with regard to the market demand function for status goods. Following Spence, who recommended the application of his Job Market Signaling to conspicuous consumption, in Mating à la Spence potential partners are faced with asymmetric information: Individuals know their own properties, but are incompletely informed about potential partners. However, individuals have the possibility to signal their properties by demonstrative consumption. Mating à la Spence provides a game theoretical derivation of the market demand function for status goods with respect to level and distribution of income in the considered economy: If (1) the price is low, everyone buys the good; if (2) the price is high, only the rich buy the good (a status good in a narrow sense). If (3) the price is located in a very high as well as in a middle range, demand drops. In addition this approach allows conclusions about the potential welfare improving impact of conspicuous consumption.
urn:nbn:de:gbv:705-opus-17088
Keywords: 330; Konsuminterdependenz; Mikroökonomische Konsumfunktion; Sozialer Status; Signalling; Spieltheorie; Theorie